Illegal Online Loans: Between Community Needs and the Weakness of Sharia Financial Literacy - Sirajuddin; Rahman, Fahrur; Ramli, Bustam (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
Access to Islamic financial services in Indonesia remains very limited. In fact, Islamic finance has a large market share across industries such as microfinance, small and medium enterprises, and retail lending. This condition has encouraged the rise of online loans as an alternative source of quick funding for business actors without considering the risks or Sharia compliance. This study aims to analyze the motives behind illegal online borrowing and the low level of Sharia financial literacy among community members. This study uses a qualitative approach with a case study design. Primary data were collected through interviews with individuals who have previously used illegal online loan services. The findings show that residents of Makassar, Maros, and Gowa generally admitted that they used online loans because the process was extremely easy, fast, and required fewer documents compared to banks. They also stated that they were not familiar with Sharia-compliant lending platforms and did not know how to distinguish between Sharia and non-Sharia online loan services. Thus, it can be concluded that transactions involving online loans in these regions are largely driven by low literacy in Islamic finance and by a consumerist lifestyle.